Dengue E Protein Domain III-Based DNA Immunisation Induces Strong Antibody Responses to All Four Viral Serotypes. - Monica Poggianella; José L Slon Campos; Kuan Rong Chan; Hwee Cheng Tan; Marco Bestagno; Eng Eong Ooi; Oscar R Burrone (Public Library of Science (PLoS), 2015)
Dengue virus (DENV) infection is a major emerging disease widely distributed throughout the tropical and subtropical regions of the world affecting several millions of people. Despite constants efforts, no specific treatment or effective vaccine is yet available. Here we show a novel design of a DNA immunisation strategy that resulted in the induction of strong antibody responses with high neutralisation titres in mice against all four viral serotypes. The immunogenic molecule is an engineered version of the domain III (DIII) of the virus E protein fused to the dimerising CH3 domain of the IgG immunoglobulin H chain. The DIII sequences were also codon-optimised for expression in mammalian cells. While DIII alone is very poorly secreted, the codon-optimised fusion protein is rightly expressed, folded and secreted at high levels, thus inducing strong antibody responses. Mice were immunised using gene-gun technology, an efficient way of intradermal delivery of the plasmid DNA, and the vaccine was able to induce neutralising titres against all serotypes. Additionally, all sera showed reactivity to a recombinant DIII version and the recombinant E protein produced and secreted from mammalian cells in a mono-biotinylated form when tested in a conformational ELISA. Sera were also highly reactive to infective viral particles in a virus-capture ELISA and specific for each serotype as revealed by the low cross-reactive and cross-neutralising activities. The serotype specific sera did not induce antibody dependent enhancement of infection (ADE) in non-homologous virus serotypes. A tetravalent immunisation protocol in mice showed induction of neutralising antibodies against all four dengue serotypes as well.